Les choses… - Pierre Curie; Laurence de Finance (In Situ)
In the culture of France’s historic monuments, as in French universities, the monumental has long been considered as more important than sculptures or works of art, generally seen as more to do with museums. In the writings and tastes of André Chastel, however, the categories were not so clear-cut and, at the French Inventory, although architecture has enjoyed a certain pre-eminence, the object, in the broadest sense of the term, has been taken into consideration form the outset. Over 17,000 items now feature in the national database Palissy, on moveable objects. The first scientific vocabulary, published by the Inventory services in 1969, was devoted to tapestry and, over the last twenty years, other vocabularies have dealt with sculpture, domestic civil furniture and stained glass.